The Modified Reasons for Smoking Scale: factorial structure, validity and reliability in pregnant smokers. Issue 3 (3rd January 2016) - De Wilde, Katrien Sophie; Tency, Inge; Boudrez, Hedwig; Temmerman, Marleen; Maes, Lea; Clays, Els
Abstract: Rationale, aims and objectives: Smoking during pregnancy can cause several maternal and neonatal health risks, yet a considerable number of pregnant women continue to smoke. The objectives of this study were to test the factorial structure, validity and reliability of the Dutch version of the Modified Reasons for Smoking Scale (MRSS) in a sample of smoking pregnant women and to understand reasons for continued smoking during pregnancy. Methods: A longitudinal design was performed. Data of 97 pregnant smokers were collected during prenatal consultation. Structural equation modelling was performed to assess the construct validity of the MRSS: an exploratory factor analysis was conducted, followed by a confirmatory factor analysis.Test–retest reliability (<16 weeks and 32–34 weeks pregnancy) and internal consistency were assessed using the intraclass correlation coefficient and the Cronbach's alpha, respectively. To verify concurrent validity, Mann–Whitney U ‐tests were performed examining associations between the MRSS subscales and nicotine dependence, daily consumption, depressive symptoms and intention to quit. Results: We found a factorial structure for the MRSS of 11 items within five subscales in order of importance: tension reduction, addiction, pleasure, habit and social function . Results for internal consistency and test–retest reliability were good to acceptable. There were significant associations of nicotine dependence with tension reduction and addiction and of daily consumption with addiction and habit . Conclusions: Validity and reliability of the MRSS were shown in a sample of pregnant smokers. T ension reduction was the most important reason for continued smoking, followed by pleasure and addiction . Although the score for nicotine dependence was low, addiction was an important reason for continued smoking during pregnancy; therefore, nicotine replacement therapy could be considered. Half of the respondents experienced depressive symptoms. Hence, it is important to identify those women who need more specialized care, which can include not only smoking cessation counselling but also treatment for depression.